The Cultivation of Character Education Values in Teachers' Directive Speech Acts in the Indonesian Language Learning Process: A Pragmatics Study - Pratama, Deni Surya; Markhamah, M (Universitas Muhammadiyah Surakarta, 2023)
The purpose of this study is to describe the types of directive speech acts employed by teachers and the character education values imparted during Class XII Indonesian language learning. The research methodology employed is qualitative research with descriptive methods. The research data encompass both primary and secondary sources. Primary data comprises direct observations, including listening, recording, and voice recording of teachers' speech during lessons. Secondary data, on the other hand, is gathered from books, e-books, and other literature sources to support the analysis of teachers' directive speech acts. The data are analyzed using the pragmatic commensurate method, where the teacher, as the speaker, delivers the speech. Data analysis involves basic techniques to identify the types of directive speech acts and character education values. The findings of this study reveal five types of directive speech acts: requests, questions, commands, prohibitions, and advice. Additionally, various character education values are identified, such as religious values, hard work, responsibility, discipline, curiosity, and independence. Teachers employ a range of directive speech acts in their Indonesian language teaching practices, integrating verbal reinforcement of character education values within these acts.